Effects of Fallow Management Practices on Soil Water, Crop Yield and Water Use Efficiency in Winter Wheat Monoculture System: A Meta-Analysis - Adil, Muhammad; Zhang, Shaohong; Wang, Jun; Shah, Adnan Noor; Tanveer, Mohsin; Fiaz, Sajid (Frontiers in Plant Science, 2022)
Winter wheat mono-culture is a common cropping system especially in dryland areas. How fallow management practices affect soil water conservation and crop yield and water use need to be synthesized. We selected 137 studies and performed a meta-analysis to test the effects of tillage and mulching during the fallow period on precipitation storage efficiency (PSE) during the fallow, soil water storage at wheat planting (SWSp), crop yield, evapotranspiration (ET) and water use efficiency (WUE). Compared to conventional tillage (CT), no tillage (NT) overall increased SWSp and PSE by 5 and 36%, respectively. Furthermore, NT no mulching, NT straw mulching and NT stubble mulching significantly increased SWS by 14, 8% and 14% respectively. However, cover cropping with NT, reduced tillage (RT) and subsoil tillage ST decreased SWSp by 14, 24 and 22% respectively. Maximum PSE (41% increase) was achieved with NT no mulching followed by NT straw mulching (25%). RT film mulching and NT film mulching increased winter wheat yield and ET by 28 and 14% respectively. There was no significant result of conservation tillage on ET compared to CT. Straw mulching significantly increased SWSp and PSE by 16 and 22% respectively. Furthermore, straw mulching NT significantly increased SWSp by 8% which greatly attributed in increasing PSE by 25% compared to bare fallow. While considering the negative effect of cover cropping on SWSp, which participated greatly in declined winter wheat yield and WUE. All types of soils showed better response of tillage and mulching methods on SWSp, PSE and winter wheat yield during fallow period, while fine and course-textured soils showed positive response ratio of conservation tillages on ET and WUE than medium-textured soils. Fine and course-textured soils showed positive response ratio of mulching on SWS, PSE and winter wheat yield than medium-textured soils. There was a significant interaction between tillage and mulching practices on SWSp, PSE and winter wheat yield with greatest increase in SWSp, PSE and winter wheat yield were obtained with NT practice.